Issues and challenges of waqf in~providing healthcare resources - Sulistyowati; Raditya Sukmana; Ririn Tri Ratnasari; Ascarya; Tika Widiastuti (Islamic Economic Studies (IES), 2022)
Purpose This paper attempts to rejuvenate waqf in the health sector by identifying and elaborating on its issues and challenges. The government budget for this sector is significant; thus, the present paper aims to provide a nongovernment budget to lessen the government's burden Design/methodology/approach This qualitative study uses structured in-depth interviews with 12 respondents to generate valuable insights and thoughts in order to frame recommendations. Findings The findings highlight the key themes: human resources, finance, collaboration and coordination, legal issues, basic healthcare insufficiency, data and digitalization, accountability and sustainability and infrastructure. The following are the proposed solutions: capacity building program (CBP), hybrid waqf scheme, big data connectivity, specific legal framework, refocusing and reallocating of resources for the health sector during and after the pandemic Research limitations/implications This study focuses on Indonesia and Malaysia as the authors believe that these two countries have a lot of practice in the field. Further studies may focus on other countries, such as Pakistan. Practical implications This paper proposes potential ways to embrace government policy consideration, optimize the elaboration among productive waqf with other kinds, improve governance of and coordination among waqf institutions and increase the awareness to improve significant development. Social implications By considering this paper's recommendations, waqf stakeholders in the healthcare system can improve the social benefits for poor and needy patients. Originality/value This study presents the latest strategic analysis of waqf, which is important for the government policy in developing waqf.
Keywords: B55; D64; I18; 330; Challenges; Healthcare; Issues; Resources; Waqf